TOXICITY AND SPR /SAR PROPERTIES OF ORGANOPHOSPHORUS INSECTICIDES USED IN AGRICULTURE - K., Guimeur1; Z., . Almi2, Belaidi2* S. (university of eloued جامعة الوادي, 2019)
The application of computational methods on the organophosphorus derivatives shows that, these toxic compounds will not have problems with oral bioavailability. The toxicity of Organophosphorus insecticide depends upon the nature and the environment of the bonds with different receptors. The P-O bond plays a very important role in the process of the poisoning action inside the body. Calculated values of bond lengths, charges, dipole moments, heats of formation, drug-likeness and SPR/SAR properties, are reported in terms of the biological property/toxicity of organophosphorus insecticides, using the following quantum methods, ab initio/HF, and DFT/ B3LYP and PM3 method.
artical
Keywords: Organophosphorus insecticide, structure, toxicity, drug-likeness, QSPR.